Efeito protetor de quercetina sobre células tubulares renais e o envolvimento com o eixo renina-angiotensina- aldosterona - Canuto, Jáder Almeida (2021)
Ischemia-reperfusion (I/R) syndrome plays an important role in acute kidney injury (AKI) due to the generation of reactive oxygen species (ROS). Antioxidant substances, especially those of natural origin, have been studied in the prevention of oxidative damage related to I/R. In this context, quercetin stands out as a flavonoid with antioxidant potential, enzyme modulator and inhibition of the Renin-Angiotensin- Aldosterone System (RAAS). The aim of this study was to evaluate the effect of quercetin on renal tubular cells subjected to I/R and to analyze the involvement of RAAS inhibition in this effect. The LLC-MK2 tubular renal cells were submitted to an in vitro ischemia/reperfusion model and then treated with quercetin at concentrations considered non-toxic. Cell viability was assessed by the 3-(4,5-Dimethylthiazol-2-yl)-2,5- Diphenyltetrazolium bromide (MTT) reduction assay. Tubular cell damage was evaluated by the release of the kidney injury molecule-1 (Kidney Injury Molecule-1 - KIM-1). Oxidative stress was assessed by the formation of thiobarbituric acid reactive species (TBARS) and accumulation of reduced glutathione (GSH). The evaluation of cell death and mitochondrial depolarization were analyzed by flow cytometry. In silico assays were carried out to evaluate the theoretical interaction of quercetin with the angiotensin- converting enzyme and with the AT1 receptor of angiotensin II. In the present work, quercetin was able to prevent oxidative damage induced in renal tubular cells after ischemic events. This potential may be related to the ability to prevent cell death after I/R, mainly by protecting mitochondria against depolarization, evidenced by the analysis of rhodamine 123 and inhibition of KIM-1 release. The effects of quercetin were compared to lisinopril and losartan, inhibitors of the renin-angiotensin system (RAAS). Lisinopril had no protective effect. Losartan had a moderate effect when compared to quercetin. In this context, molecular docking simulations showed that quercetin has the potential to interact with the angiotensin AT1 receptor with greater affinity, presenting a stable bond through the formation of five strong hydrogen bonds. Thus, our results suggest that quercetin had a protective effect on LLC-MK2 cells with RAAS involvement, by blocking AT1 receptors.